GENERIC DRUG REGISTRATION AND COUNTRY-SPECIFIC REQUIREMENTS IN SAUDI ARABIA, QATAR, BAHRAIN, AND OMAN - J., GUNASEELAN; K. M., ASHA SPANDANA (International Journal of Pharmacy and Pharmaceutical Sciences, 2024)
Objective: This research aims to examine the regulatory framework and prerequisites for generic drug registration in the Middle East and North Africa (MENA) region, with a specific focus on the countries that make up the Gulf Cooperation Council (GCC). This will enable a deeper understanding of the procedures, records, schedules, and discrepancies related to registration. Methods: The study makes use of an extensive examination of the rules, regulations, and practices about the registration of generic drugs in the MENA. Official government sites, regulatory agencies, and respectable trade journals for the pharmaceutical sector were used as sources of information. The main procedures for registering generic drugs were explained and inspected, encompassing the submission of documents, dossier preparation, bioavailability/bioequivalence tests, and application filing. Results: There are substantial growth prospects for generics. Research highlights the sequential registration process for generic drugs, submitting documents electronically using the Common Technical Document (eCTD) method. For registration to be successful, specific records and data such as bioavailability/bioequivalence research data must be provided. Conclusion: The effective registration of generic medications in the MENA region, especially in the GCC nations, depends on understanding and abiding by nation-specific regulatory standards. The research offers a tactical guide that outlines the essential procedures, paperwork needs, and regional variances in the generic medicine registration process. The goal is to offer affordable healthcare solutions by navigating the regulatory landscape meticulously and streamlining the approval and market entry process for generic pharmaceuticals in the MENA region.